WORD-FORMING SEMANTICS OF ADJECTIVES IN DENUMERATIVE WORD-FORMATION - Kostryba, O. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The article examines the denumerative semantics of the adjectival class of words of the Ukrainian language, which was caused by the completeness of taking into account the functional expression of the forming base, in particular the numeral one, along with the formant-centric aspect of the study of word-formation. The purpose of the proposed work is to find out the word-forming meanings of derived substantives in the denumerative word-formation of the modern Ukrainian language. During the work, the linguistic structural-semantic method was applied in combination with the use of paraphrases, as well as the general scientific descriptive method and the use of quantitative calculations. The result of scientific research is the established word-forming meanings ​​of the derivatives of the adjectival block in denumerative word-formation, which is interpreted on the basis of sixteen word-forming nests with numeral vertices. Taking into account the structural features of the motivational base, the word-forming semantics is analyzed taking into account its onomasiological manifestation, as well as the unifying content of the semantics of the motivational components. Thus, the types of derivation within each word-forming meaning (mutational, modificational, complicated, and uncomplicated syntagmatic types) were determined, and word-forming models were identified. The scientific novelty of the study consists in establishing and typologizing the word-forming semantics of the adjectival block of denumerative word-formation, considered through the prism of foundation-centric teachings. The obtained results can serve as material for the development of specialized courses and seminars in universities, be used in the scientific works of word-formation researchers, and also in the process of creating word-formation diсtionaries.